2018
DOI: 10.4266/acc.2018.00367
|View full text |Cite
|
Sign up to set email alerts
|

Critical Care before Lung Transplantation

Abstract: Lung transplantation is widely accepted as the only viable treatment option for patients with end-stage lung disease. However, the imbalance between the number of suitable donor lungs available and the number of possible candidates often results in intensive care unit (ICU) admission for the latter. In the ICU setting, critical care is essential to keep these patients alive and to successfully bridge to lung transplantation. Proper management in the ICU is also one of the key factors supporting long-term succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The most significant risk factor for hospital-acquired pneumonia is mechanical ventilation, and prolonged intubation increases the risk of ventilator-associated pneumonia [ 34 ]. These infections increase the risk of failure of bridges to LTx in patients with end-stage lung disease and increase the risk of mortality after LTx [ 35 ]. A study of awake ECMO as a bridge to heart transplantation showed a lower incidence of pneumonia compared to non-awake ECMO group [ 36 ].…”
Section: Advantages Of Awake Ecmomentioning
confidence: 99%
“…The most significant risk factor for hospital-acquired pneumonia is mechanical ventilation, and prolonged intubation increases the risk of ventilator-associated pneumonia [ 34 ]. These infections increase the risk of failure of bridges to LTx in patients with end-stage lung disease and increase the risk of mortality after LTx [ 35 ]. A study of awake ECMO as a bridge to heart transplantation showed a lower incidence of pneumonia compared to non-awake ECMO group [ 36 ].…”
Section: Advantages Of Awake Ecmomentioning
confidence: 99%
“…Most countries use lung allocation scores or priority organ allocation systems based on a combination of waitlist urgency and the probability of post-transplant survival. However, in South Korea, the priority of the organ allocation system of the government is predominantly determined by the emergency of a patient’s status, and this is justified by ethical principles [ 26 ]. For these reason, the percentage of patients requiring ECMO bridge to LTx is high, up to 26.5%.…”
Section: Discussionmentioning
confidence: 99%
“…However, in South Korea, organ allocation is governed primarily by the urgency of a patient's status. [30].…”
Section: Discussionmentioning
confidence: 99%